Exertional Stress-induced Pathogenic Luminal Content Translocation – Friend or Foe? - Henningsen, Kayla; Martinez, Isabel; Costa, Ricardo J. S. (International Journal of Sports Medicine, 2024)
The incidence of perturbed gastrointestinal integrity, as well as resulting systemic immune responses and gastrointestinal symptoms, otherwise known as exercised-induced gastrointestinal syndrome (EIGS), is common among individuals who partake in prolonged exercise. EIGS may cause the translocation of pathogenic material, including whole bacteria and bacterial endotoxins, from the lumen into circulation, which may progress into clinical consequences such as sepsis, and potentially subsequent fatality. However, further investigation is warranted to assess the possibility of food allergen and/or digestive enzyme luminal to circulatory translocation in response to exercise, and the clinical consequences. Findings from this narrative literature review demonstrate evidence that whole bacteria and bacterial endotoxins translocation from the gastrointestinal lumen to systemic circulation occurs in response to exercise stress, with a greater propensity of translocation occurring with accompanying heat exposure. It has also been demonstrated that food allergens can translocate from the lumen to systemic circulation in response to exercise stress and initiate anaphylaxis. To date, no research investigating the effect of exercise on the translocation of digestive enzymes from the lumen into systemic circulation exists. It is evident that EIGS and consequential pathogenic translocation presents life-threatening clinical implications, warranting the development and implementation of effective management strategies in at-risk populations.
Keywords: gastrointestinal symptoms; intestinal epithelium; systemic inflammation; auto-digestion; exercise-induced anaphylaxis; exertional-heat stress